2011
DOI: 10.1007/s00592-011-0327-4
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus and celiac disease: endothelial dysfunction

Abstract: In the observational study cited above, we evaluated whether the presence of undiagnosed CD in a group of adult DM1 patients is associated with a different expression of some hemostatic factors, as well as with a different manifestation and/or progression of microvascular complications in comparison with patients suffering from DM1 only. The Ventura group has carefully examined and commented on this study, but we are only partially in agreement with their observations. First, the including criterion HbA1c B 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Research has largely focused on studying the prevalence of CD in T1D (8,9), as well as the benefits of starting a gluten-free diet in asymptomatic CD within the T1D population (9,22). Few studies have examined the risk of complications in patients with both conditions (10,11,23), and none have thus far been able to determine time-specific risks for T1D complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has largely focused on studying the prevalence of CD in T1D (8,9), as well as the benefits of starting a gluten-free diet in asymptomatic CD within the T1D population (9,22). Few studies have examined the risk of complications in patients with both conditions (10,11,23), and none have thus far been able to determine time-specific risks for T1D complications.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia and hypertension increase the risk of DRP (3). Recently, Picarelli et al (10) demonstrated that patients with T1D and CD had lower levels of HbA 1c , triglycerides, and cholesterol than patients with only T1D. These researchers (10) found no signs of retinal or renal abnormalities in patients with T1D and CD (10), but the study was cross-sectional without follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ieko et al [58] reported that aPS/PT IgG recognizes prothrombin bound to phosphatidylserine on platelets and endothelial cells and, directly or via Fc-gamma receptors, activates a variety of procoagulant agents. However, the complementary aspects of CD are endothelial dysfunction [59], platelet abnormalities [60,61] and increased apoptosis [62]. Thus, it is suggested that intestinal injury, endothelial dysfunction, platelet abnormalities and enhanced apoptosis cause increased exposure of phospholipids or new epitopes, which are the origin of aPT, aPL and aPS/PT autoantibodies.…”
Section: Discussionmentioning
confidence: 99%